2019
DOI: 10.1021/acs.jmedchem.8b01408
|View full text |Cite
|
Sign up to set email alerts
|

Triazole-Based Inhibitors of the Wnt/β-Catenin Signaling Pathway Improve Glucose and Lipid Metabolisms in Diet-Induced Obese Mice

Abstract: Wnt/β-catenin signaling pathway is implicated in the etiology and progression of metabolic disorders. While lines of genetic evidence suggest that blockage of this pathway yields favorable outcomes in treating such ailments, few inhibitors have been used to validate the promising genetic findings. Here, we synthesized and characterized a novel class of triazole-based Wnt/βcatenin signaling inhibitors, and assessed their effects on energy metabolism. One of the top inhibitors, compound 3a, promoted Axin stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Cell lysates were prepared using NP-40 lysis buffer as previously described [ 16 ]. The lysate was centrifuged at 14,000× g for 15 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell lysates were prepared using NP-40 lysis buffer as previously described [ 16 ]. The lysate was centrifuged at 14,000× g for 15 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Cell lysates were prepared using NP-40 lysis buffer as previously described [16]. The lysate was centrifuged at 14,000× g for 15 min at 4 • C. Bicinchoninic acid (BCA) assay was used to normalize protein concentrations across the samples, and the proteins were resolved on a 7.5-12% SDS-PAGE gels.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A library of 1-benzyl-N-(2-(phenylamino)pyridin-3-yl)-1H-1,2,3-triazole-4-carboxamides was screened for their antiproliferative activity and showed promising cytotoxicity against lung cancer cell line A549 (Prasad et al, 2019). In addition to the antitumor studies, 1H-1,2,3-triazole-4-carboxamides exhibit other biological activities such as fungicidal (Wang et al, 2014), antiviral (Krajczyk et al, 2014) and antimicrobial (Jadhav et al, 2017) activities and were found to be inhibitors of the Wnt/catenin signalling pathway (Obianom et al, 2019). It should be noted that the diversity of such compounds can be obtained by amidation of 1H-1,2,3-triazole-4-carboxylic acids prepared by convenient Dimroth synthesis and further modifications (Pokhodylo et al, 2009(Pokhodylo et al, , 2017(Pokhodylo et al, , 2018Pokhodylo, Savka et al, 2010;.…”
Section: Chemical Contextmentioning
confidence: 99%
“…23 Some 1,2,3-triazoles recently described as inhibitors of the wnt/β-catenin signaling pathway. 24 In addition, celecoxib as a sulfonamide selective COX-2 inhibitor inhibited human colon cancer cell proliferation by suppressing the Wnt/β-catenin signaling pathway. 25 Because of the same 1,2,3-triazole scaffold in the hybrid 7c, we also explored its effects on the wnt/β-catenin signaling pathway.…”
Section: Benzenesulfonamide Hybrid 7c Affected the Wnt/β-catenin/gsk3mentioning
confidence: 99%